2013
DOI: 10.1038/cr.2013.37
|View full text |Cite|
|
Sign up to set email alerts
|

The mitochondrial genome encodes abundant small noncoding RNAs

Abstract: Small noncoding RNAs identified thus far are all encoded by the nuclear genome. Here, we report that the murine and human mitochondrial genomes encode thousands of small noncoding RNAs, which are predominantly derived from the sense transcripts of the mitochondrial genes (host genes), and we termed these small RNAs mitochondrial genome-encoded small RNAs (mitosRNAs). DICER inactivation affected, but did not completely abolish mitosRNA production. MitosRNAs appear to be products of currently unidentified mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(165 citation statements)
references
References 71 publications
5
158
1
1
Order By: Relevance
“…The studies suggested the presence of unique class of small RNAs in the human mitochondria (Mercer et al, 2011;Ro et al, 2013). Apart from this, a subset of the nuclear encoded microRNAs have been shown to localize to the mitochondria (Das et al, 2012).…”
Section: Mito-mirs and The Emerging Evidence Of Noncoding Rna Epigenementioning
confidence: 97%
“…The studies suggested the presence of unique class of small RNAs in the human mitochondria (Mercer et al, 2011;Ro et al, 2013). Apart from this, a subset of the nuclear encoded microRNAs have been shown to localize to the mitochondria (Das et al, 2012).…”
Section: Mito-mirs and The Emerging Evidence Of Noncoding Rna Epigenementioning
confidence: 97%
“…Two biological replicates of FACS-purified Sertoli cells from control, Dicer cKO, and Drosha cKO testes (n Ï­ 2) were sequenced using the Ion Torrent Personal Genome Machine (PGM) (Invitrogen) as described (17,18). Briefly, sncRNAs were isolated using the mirVana miRNA isolation kit (Invitrogen), and cDNA libraries were generated using the Ion Total RNA-Seq kit v2 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the mitochondrial genome encodes mitosRNAs in animals. However, the mapped L. striatellus sRNAs had peaks at 22 nt (unique reads) and 23 nt (redundant reads) (Figure S1), which was different from the peak at 30 nt observed in the human and mouse genomes [38]. Thus, it can be concluded that different mechanisms may be used to produce mitosRNAs in different species [38].…”
Section: Resultsmentioning
confidence: 77%